Picosecond Wavelength Conversion Using Semiconductor Optical Amplifier Integrated with Microring Resonator Notch Filter - Razaghi, M.; Gandomkar, M.; Ahmadi, Y.; Das, Narottam; Connelly, M. (Springer, 2012)
In this paper, we analyse the picosecond wavelength conversion using semiconductor optical amplifier (SOA) with a novel technique. For an accurate and precise modelling, all the nonlinear effects that are relevant to picosecond and subpicosecond pulse regime, such as, self-phase modulation, nonlinear Kerr effect, spectral hole burning, carrier heating, carrier depletion, two-photon absorption and group velocity dispersion are taken into account in the SOA model. We integrate the structure with a microring resonator notch filter to eliminate the unwanted pump and probe signals at the output of the system. It shows that with the three coupled microring resonators, output four-wave mixing (FWM) signal generated by the SOA can be filtered accurately. Moreover, our results demonstrate that the microring resonator can be used for modifying the shape and spectrum of the output FWM signal. Simulation results show that this new technique enhances the output time bandwidth product.